Multifunctional rare earth molecular ferroelectrics with a piezoelectric response: ((nBu)4N)3[Ce(NO3)4(SCN)2]((CH3CH2CH2CH2)4N = tetrabutylammonium). Issue 46 (5th November 2021) - Ying, Tingting; Tan, Yuhui; Tang, Yunzhi; Long, Xiao; Song, Ning; Li, Yukong; Sun, Zhen
Abstract : A new type of multipolar rare earth molecular ferroelectric: (( n Bu)4 N)3 [Ce(NO3 )4 (SCN)2 ] (BuCH3 CH2 CH2 CH2 )4 N), undergoes a high-temperature ferroelectric phase transition, possesses flexible switchable SHG effect, moderate spontaneous polarization and a narrow band gap. Abstract : Piezoelectric responsive molecular ferroelectrics have become a research hotspot due to their advantages of simple fabrication, environmental friendliness, light weight and good mechanical flexibility. Here we proposed a new kind of multipole rare earth molecular ferroelectric, (( n Bu)4 N)3 [Ce(NO3 )4 (SCN)2 ]((CH3 CH2 CH2 CH2 )4 N = tetrabutylammonium) (1 ). Compound 1 undergoes a high temperature ferroelectric phase transition at 408 K. It is worth noting that compound 1 has a narrow band gap of 2.61 eV, flexible switchable SHG effect, moderate spontaneous polarization P s = 3.6 μC cm −2, and piezoelectric constant = 3 pC N −1 . The results show that these findings provide ideas for exploring multifunctional rare earth molecular ferroelectrics with a piezoelectric effect.